A Preliminary Investigation of a Specialized Music Therapy Model for Children with Disabilities Delivered in a Classroom Setting. (23rd November 2016) - Mendelson, Jenna; White, Yasmine; Hans, Laura; Adebari, Richard; Schmid, Lorrie; Riggsbee, Jan; Goldsmith, Ali; Ozler, Burcu; Buehne, Kristen; Jones, Sarah; Shapleton, Jennifer; Dawson, Geraldine
Abstract : Music therapy is gaining popularity as an intervention strategy for children with developmental disabilities, including autism spectrum disorder (ASD). This study was a pilot investigation of a classroom-based music-based intervention, Voices Together®, for improving communication skills in children with ASD and children with intellectual disabilities. Four local public elementary school special education classrooms, serving 5 children with a classification of autistic disorder and 32 children with intellectual disability without autism, were randomly selected to receive one of two levels of exposure to Voices Together music therapy: "long-term" (15 weeks beginning in January 2015 (Time 1), n = 14 ) or "short-term" (7 weeks beginning 7 weeks later in February (Time 2), n = 17 ). Using observational ratings, investigators reliably scored participants live in terms of their level of verbal responsiveness to prompts during three songs featured each week of the program. Both groups demonstrated increases in verbal responses over time; however, only the long-term group demonstrated significant within-group increases. Preliminary findings suggest that music therapy delivered in a classroom in 45-minute weekly sessions for 15 weeks can promote improvements in verbal responsiveness among individuals with autism and other developmental disabilities. Findings warrant further investigation into the efficacy of classroom-based music therapy programs.